Fluorescent small-molecule agonists as follicle-stimulating hormone receptor imaging tools. Issue 4 (3rd August 2020) - Hoogendoorn, Sascha; van Puijvelde, Gijs H. M.; van der Marel, Gijs A.; van Koppen, Chris J.; Timmers, C. Marco; Overkleeft, Herman S.
Abstract : Discovery of a potent, small-molecule, fluorescent agonist of the follicle-stimulating hormone receptor (FSHR) for selective staining of FSHR-expressing cells. Abstract : Fluorescent cell surface receptor agonists allow visualization of processes that are set in motion by receptor activation. This study describes the synthesis of two fluorescent, low molecular weight ligands for the follicle-stimulating hormone receptor (FSHR), based on a dihydropyridine (DHP) agonist. We show that both BODIPY- and Cy5-conjugated DHP ( m -DHP-BDP and m -DHP-Cy5) are potent FSHR agonists, able to activate receptor signalling with nanomolar potencies and to effect receptor internalisation at higher concentrations. FSHR-dependent uptake of m -DHP-Cy5 is in stark contrast to the cellular uptake of m -DHP-BDP which was efficiently internalised also in the absence of FSHR. Our results comprise a first-in-class fluorescent low molecular weight ligand for in situ FSHR imaging and pertain the potential means for targeted delivery of drugs into the endolysosomal pathway of FSHR-expressing cells.